1198. Clinical Characteristics and Outcomes of Klebsiella pneumoniae Infections in Service Members Who Sustained Trauma in Iraq and Afghanistan. (26th November 2018) - Kiley, John; Mende, Katrin; Kaiser, Susan J; Carson, Leigh; Lu, Dan Z; Whitman, Timothy J; Petfield, Joseph L; Tribble, David R; Blyth, Dana M
Abstract: Background: Klebsiella pneumoniae infections present a challenge to the clinician due to increasing resistance. K. pneumoniae was the third most common species of multidrug-resistant (MDR) Gram-negative organism in trauma patients sustaining injuries in Iraq and Afghanistan from 2009 to 2014. This study aims to elucidate the epidemiology of these infections by characterizing clinical aspects, risk for MDR infections, and outcomes. Methods: All initial and serial (≥7 days from prior isolate) infecting K. pneumoniae isolates were collected from the Trauma Infectious Disease Outcomes Study (TIDOS) (6/09-12/14). Antimicrobial susceptibilities were determined using the BD Phoenix Automated Microbiology System and CLSI criteria. MDR was defined as either resistance to ≥3 classes of aminoglycosides, β-lactams, carbapenems and/or fluoroquinolones or production of an ESBL or KPC. Results: Of 588 K. pneumoniae isolates in the TIDOS registry, 141 infecting isolates (98 initial) from 51 patients met inclusion criteria. Initial isolates were respiratory (31%), wound (25%), blood (20%), urine (10%), intra-abdominal (8%) and other (6%). All patients were male with a median age of 23 years (IQR 21–28). The majority of patients (82%) suffered blast injuries; of which, 88% were from improvised explosive devices. Patients had a median injury severity score (ISS) of 38 (IQR 30–45) and time from injury to first infecting K. pneumoniae isolate was 15 days (IQR 8–31). The median hospital stay was 49 days (IQR 28–70) and four patients died. All patients had received antibiotics prior to diagnosis. Twenty-three (46%) patients had initial isolates classified as MDR. There was no difference in age, ISS, or time from injury to first isolation among those who did and did not have initial MDR isolates. Sixteen patients had 64 serial isolates, of which 24 were wound, 20 respiratory, 14 blood and six urine. Three of these 16 patients died compared with 1 of 35 patients without serial isolates. Conclusion: K. pneumoniae infections are common among combat casualties. Patients with K. pneumoniae infections were severely injured and almost half of initial infecting isolates were MDR, complicating treatment. Disclosures: All authors: No reported disclosures.